Characterization, tissue distribution, and expression of neuropeptide Yin olive flounder Paralichthys olivaceus - 王倩 谭训刚 杜少军 孙威 尤锋 张培军 (中国海洋湖沼学报：英文版, 2015)
Neuropeptide Y （NPY） is a 36-amino acid peptide of the neuropeptide Y family that plays key roles in the regulation of food intake. In this study, we focused on NPY mRNA expression changes around feeding time and during food deprivation in olive flounder. The olive flounder NPY mRNA levels were analyzed in different tissues and a high level of expression was detected in the brain. We also demonstrated a correlation between NPY expression levels in the brain and feeding schedule. NPY expression levels in olive flounder maintained on a daily scheduled feeding regimen increased shortly before feeding and decreased after the scheduled feeding time. Compared with the -1 h group before feeding, NPY expression in the 3 h group after feeding decreased significantly （P〈0.05）. Food deprivation led to an 81.7% decrease in NPY mRNA levels in the 24 h fasted group （P〈0.05） and a 91.7% decrease in the 48 h fasted group （P〈0.05）. Therefore, our study demonstrates that NPY expression is associated with food intake in olive flounder. This result reveals the function of NPY in regulating food intake and its potential importance in olive flounder aquaculture.